5(x+3)+2=(x+7)

Simple and best practice solution for 5(x+3)+2=(x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+3)+2=(x+7) equation:



5(x+3)+2=(x+7)
We move all terms to the left:
5(x+3)+2-((x+7))=0
We multiply parentheses
5x-((x+7))+15+2=0
We calculate terms in parentheses: -((x+7)), so:
(x+7)
We get rid of parentheses
x+7
Back to the equation:
-(x+7)
We add all the numbers together, and all the variables
5x-(x+7)+17=0
We get rid of parentheses
5x-x-7+17=0
We add all the numbers together, and all the variables
4x+10=0
We move all terms containing x to the left, all other terms to the right
4x=-10
x=-10/4
x=-2+1/2

See similar equations:

| 2x²+1x+15=0 | | T+4h=38 | | 1/10x+3/2=-1/5 | | 5x+25=8×-(-9) | | 4(x-2)+7-3x=45 | | P=3×+3y | | 12^3-x=36 | | 4t+14=5-7 | | x^2/6+x/2+1/3=0 | | 16.8-v=3v | | 7m+2=-40 | | 25x+(-8)=2+16x | | -150x+49=-115x+21 | | y-y(.33)=167.50 | | 3.2a-24=4a | | 10=4+3(t+2 | | 9-150x+40=0 | | 30+17x=5x+2 | | x^/6+x/2+1/3=0 | | 4x^2+3-85=0 | | 3x-42=-7x+28 | | 21-15x-100x=0 | | -9+10k=51 | | -1/x^2=2,5x-5.25 | | -3+13=5x+21 | | 2x-1=-12x+15 | | 3/4(12x-8)=18 | | -2(7-2k)-4(k-7)=14 | | 2^x=65 | | 7x=2x-34 | | -3y+15=2y-20 | | 2x-10=-4x+8 |

Equations solver categories